2017
DOI: 10.1002/cssc.201700474
|View full text |Cite
|
Sign up to set email alerts
|

Interconnected 3 D Network of Graphene‐Oxide Nanosheets Decorated with Carbon Dots for High‐Performance Supercapacitors

Abstract: Interconnected 3 D nanosheet networks of reduced graphene oxide decorated with carbon dots (rGO/CDs) are successfully fabricated through a simple one-pot hydrothermal process. The as-prepared rGO/CDs present appropriate 3 D interconnectivity and abundant stable oxygen-containing functional groups, to which we can attribute the excellent electrochemical performance such as high specific capacitance, good rate capability, and great cycling stability. Employed as binder-free electrodes for supercapacitors, the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(45 citation statements)
references
References 57 publications
0
45
0
Order By: Relevance
“…[4][5][6] Owing to these excellent properties, CQDs are widely used in medical imaging technology, [7,8] environmentalm onitoring, [9,10] chemical analysis, [11] catalystp reparation, [12,13] and energy development fields. [14,15] At present, there are two main classical routest oo btain CQDs. The "topdown"p hysical or chemical cutting strategy uses large-size carbon-based materials as precursors, such as graphene oxide sheets, carbon nanotubes, carbon fibers, or graphite.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Owing to these excellent properties, CQDs are widely used in medical imaging technology, [7,8] environmentalm onitoring, [9,10] chemical analysis, [11] catalystp reparation, [12,13] and energy development fields. [14,15] At present, there are two main classical routest oo btain CQDs. The "topdown"p hysical or chemical cutting strategy uses large-size carbon-based materials as precursors, such as graphene oxide sheets, carbon nanotubes, carbon fibers, or graphite.…”
Section: Introductionmentioning
confidence: 99%
“…2a shows that the current density of H-SCs generally increases with the printing time. The CV curves display a little deviation from rectangular shape, which may be explained by the redox reaction of oxygen-containing functional groups in the printed electrodes from the Hink [29,31,35]. The GCD curves in Fig.…”
Section: Resultsmentioning
confidence: 94%
“…It was reported that the labile epoxy and hydroxyl groups can transform to more stable C=O group by heat treatment at 200°C [43][44][45], which may be further reduced at higher temperatures. The high fraction of the C=O groups in annealed H-ink at 200°C may explain the excellent electrochemical performance of H-SCs-200, as it has been reported that the existence of stable oxygencontaining functional groups (C=O) is beneficial to the pseudocapacitance and rate capability [29][30][31].…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations